PENGARUH BUDAYA ORGANISASI DAN PENGENDALIAN INTERNAL TERHADAP KUALITAS PENGADAAN BARANG/JASA: PENELITIAN PADA BADAN LITBANG ESDM - RAMDHANA, ARDI FAJAR RAMDHANA ([Yogyakarta] : Universitas Gadjah Mada, 2015)
This study discusses the influence of Organizational Culture and Internal Control of the Quality of Goods / Services procurement in the Agency for Research and Development of Energy and Mineral Resources, Ministry of Energy and Mineral Resources. Hopefully this research can show the positive influence of Organizational Culture and Internal Control of the Quality of Goods / Services procurement. In addition it is expected to provide recommendations to the leadership in policy-making related to advancement of the organization. The method of research is done by analyzing the data and confirmed with a questionnaire and literature study. The approach used is quantitative descriptive design. Based on the research result shows that only Internal Control has an influence to the Quality of Goods / Services procurement. While the organizational culture does not have the effect of influence Quality Goods / Services procurement